Community Empowerment of Tourism Villages Through the Utilization of Mangoes into Dodol in Wonokerto Village, Pasuruan Regency - Achmad Yusuf (LPPM Universitas Yudharta Pasuruan, 2022)
This service is expected to be able to develop community capacity building by emphasizing on the development of alternative economic-based empowerment models. The Service Team carries out community service activities in Wonokerto Village, Sukorejo District, because Wonokerto Village is one of the villages that has the potential for mangoes, because most of the residents work as mango farmers. This is supported by data on the number of mango farmers in Wonokerto Village. The focus of the activities carried out by the service team is the formation of tourism awareness groups through the potential of mangoes. This assistance applies the Asset Based Community Development mentoring method, because this service carries out development based on existing assets in the Wonokerto village. The results achieved in this assistance are: the operation of a tourism awareness group through the socialization of the service team with village officials. Processing of mangoes into Dodol Mango products. And promotion of Dodol Mangga products through social media.